IMPLEMENTASI METODE TOPSIS PADA SPK PENENTUAN PENERIMA BEASISWA DI IST AKPRIND BERBASIS WEB - Agetia, I Wayan Aries; ., Suraya; Rachmawati, Rr. Yuliana (Jurnal Script, 2015)
ABSTRACTThe selection process of determining scholarship recipients candidates in Bagian Kemahasiswaan dan Alumni at Institut Sains dan Teknologi AKPRIND Yogyakarta only be done by calculating the average of all criteria to implement into the form of a Ms.Excel. During this time, there are still lacking proper selectors for selecting applicants because only rely on the manual method, so itâs canât assess applicants objectively. And so we need a system that is able to assist and support the decision of selectors. This application is designed using diagams context and data flow diagrams, while in programming using PHP programming language with application PHP Data Object as a connection to the MySQL database and using Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). The results of this design in the form of web-based applications which focused on decision making. The use of the method Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) in decision support system scholarship recipients Peningkatan Prestasi Akademik (PPA) and Bantuan Belajar Mahasisswa (BBM) is able to provide the best alternative based on the results of the highest ranking.Â Keywords: Scholarship, Decision Support Systems, TOPSIS (Technique For Others Preference by Similarity to Ideal Solution), PHP, MySQL